2008
DOI: 10.1007/s00240-008-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

A neural model for chronic pain and pain relief by extracorporeal shock wave treatment

Abstract: The paper develops a new theory of chronic pain and pain relief by extracorporeal shock wave treatment. Chronic pain without underlying anatomical disorder is looked at as a pathological control function of memory. Conditioned reXexes are considered to be engraved memory traces linking sensory input of aVerent signals with motor response of eVerent signals. This feature can be described by associative memory functions of the nervous system. Some conditioned reXexes may cause inappropriate or pathological react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 24 publications
1
44
0
2
Order By: Relevance
“…A number of studies in animals have shown that EWST results in changes in the expression of specific pain markers, such as substance P and calcitonin gene-related peptide (CGRP) in the spinal cord [35][36][37]. Wess [38] has suggested that EWST may disrupt the neural circuitry giving rise to chronic pain and thereby lead to pain relief.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies in animals have shown that EWST results in changes in the expression of specific pain markers, such as substance P and calcitonin gene-related peptide (CGRP) in the spinal cord [35][36][37]. Wess [38] has suggested that EWST may disrupt the neural circuitry giving rise to chronic pain and thereby lead to pain relief.…”
Section: Discussionmentioning
confidence: 98%
“…Some clinical studies have investigated the effects principally on AVN of the hip and they found a significant improvement in pain and in functionality without substantial changes of lesion on radiograph and MRI (Wang et al 2005. Therefore, these articles suggest that extracorporeal shock wave treatment may reorganize pathologic memory traces, thus, giving cause to real and permanent pain relief (Wess 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism involves the effect on neuroplasticity of the human pain memory and hence alternating the threshold of the pain memory and resetting the tolerance level as described by Wess . In a human neurological hologram, chronic pelvic pain may be represented by a reflex pattern between pain sensation and muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism involves the effect on neuroplasticity of the human pain memory and hence alternating the threshold of the pain memory and resetting the tolerance level as described by Wess. 10 In a human neurological hologram, chronic pelvic pain may be represented by a reflex pattern between pain sensation and muscle contraction. The use of hyperstimulation shock wave may modulate the reflex cycle by introducing strong sensor input but weak motor output, thus erasing the old reflex pattern in chronic pelvic pain.…”
Section: Discussionmentioning
confidence: 99%